Togo : Seconde Revue de l'Accord au Titre de la Facilite Elargie de Credit et Demande de Modification des Criteres de Realisation. (IMF Staff Country Reports; Country Report ;, 2018)
Economic activities have weakened due to the continuing socio-political tensions. Despite the ensuing revenue underperformance, the fiscal position improved significantly as expenditure was curtailed; the domestic primary balance at end-2017-the fiscal indicator under the direct control of the government-improved by about 5 percentage points of GDP relative to 2016. Inflation has been subdued and is expected to remain below the WAEMU convergence criterion of up to 3 percent during the program period. The current account balance has improved, driven by lower imports related to public investments. The political dialogue has stalled and protests resumed.